Cooperative catalysis of N-heterocyclic carbene and Brønsted acid for a highly enantioselective route to unprotected spiro-indoline-pyrans1. Issue 39 (14th May 2015) - Lin, Youqiang; Yang, Limin; Deng, Yue; Zhong, Guofu
<x xml:space="preserve">Abstract</x> A chiral cooperative catalysis of NHC and Brønsted acid for a formal [4+2] reaction of unprotected isatins and enals was developed for the direct synthesis of unprotected spiro[indoline-3, 2′-pyran]-2, 6′(3′H)-diones in good to excellent yields (up to 95%) with high enantioselectivities (up to >93% ee).